Canola Cost-Return Budget in Central Kansas - Warmann, Gerald W. (My University, 1999)
This publication contains information for a projected budged reflecting expected income and cost based on canola production practices in central Kansas.
MF2421_1999_10
Keywords: MF2421; Crops; Economics; MF